Visual analysis of contagion in networks. (April 2015) - von Landesberger, Tatiana; Diel, Simon; Bremm, Sebastian; Fellner, Dieter W
Contagion is a process whereby the collapse of a node in a network leads to the collapse of neighboring nodes and thereby sets off a chain reaction in the network. It thus creates a special type of time-dependent network. Such processes are studied in various applications, for example, in financial network analysis, infection diffusion prediction, supply-chain management, or gene regulation. Visual analytics methods can help analysts examine contagion effects. For this purpose, network visualizations need to be complemented with specific features to illustrate the contagion process. Moreover, new visual analysis techniques for comparison of contagion need to be developed. In this paper, we propose a system geared to the visual analysis of contagion. It includes the simulation of contagion effects as well as their visual exploration. We present new tools able to compare the evolution of the different contagion processes. In this way, propagation of disturbances can be effectively analyzed. We focus on financial networks; however, our system can be applied to other use cases as well.